2018
DOI: 10.1088/1361-6579/aaa925
|View full text |Cite
|
Sign up to set email alerts
|

Detection rate of fetal distress using contraction-dependent fetal heart rate variability analysis

Abstract: Our results show that combining contraction-dependent HRV features with HRV features calculated over the entire fetal heart rate signal improves the detection rate of fetal distress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 42 publications
2
24
0
3
Order By: Relevance
“…Then, by including features extracted from resting periods, the classification performance increased to 83.2%. These results coincide with recent, similar research, which has shown that considering features extracted from the entire FHR segment and contraction-dependent features, the classification performance improved to 79% [19].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Then, by including features extracted from resting periods, the classification performance increased to 83.2%. These results coincide with recent, similar research, which has shown that considering features extracted from the entire FHR segment and contraction-dependent features, the classification performance improved to 79% [19].…”
Section: Discussionsupporting
confidence: 92%
“…The results coincide with a recent approach [19], which employs another database, but similar class formation criteria and evaluation. That research shows that, considering features extracted from the entire FHR segment in combination with contraction-dependent features, might improve the detection of fetal distress, whose classification performance, based on the geometric mean, improved from 70% to 79%.…”
Section: Features Evaluation and Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…We found the computerized identification of FHR characteristics for the afECG technique was in most instances more faithful to results from the scalp electrode than US-based FHR detection in the identification of baseline heart rate, and heart rate variability, ac- pattern interpretation, [28][29][30] This is the first study to address whether afECG monitoring produces FHR patterns that would be interpreted in the same manner as those produced by US-based cardiotachometry. Of concern in designing this study was the fact that there is considerable inter-and intra-observer variation in the visual interpretation of FHR patterns.…”
Section: Discussionmentioning
confidence: 81%
“…Current recommendations for the clinical assessment of variability in the interpretation of FHR patterns require making fine distinctions in the degree of variability observed. Because such distinctions have a potentially substantial influence on decision‐making, and because they are a component of all extant systems for FHR pattern interpretation, it is critically important that the technique used to assess rate and variability provide the most accurate available information. It has been assumed since the introduction of autocorrelation techniques to cardiotachometer software that US‐derived FHR patterns can be assumed to display true FHR variability.…”
Section: Discussionmentioning
confidence: 99%